Penilaian Portofolio Pada Aspek Kognitif, Afektif, Dan Psikomotor Siswa Tunagrahita Ringan - Ngusman, ; Wardatul Firdausi, (Pendidikan Luar Biasa, 2008)
In recent time assessment type on special school score only with number only, so the need and advancement of students can not be known by the parents or the teacher. The objective of this study is students in SLB C Bina Bangsa Taman Sidoarjo. This study uses Classroom Action Research Design. Instrument which is used on this study i.e: Lesson Plan, Observation sheet, Activity Students Sheet (LKS), and Teacher Respon Sheet.Based on the data result analysis evaluation on cognitive aspect on 1st cycle can be summarized that the students ability 70% and 2 nd cycle the ability of students in increased to 80%. The result of afective aspect in the 1st cycle is 70% and 2nd cycle the ability students increase 80%. Psychomotor aspect in 1st cycle 70% and the ability students  and 2nd cycle increase 80%. The result of this study is increasing significantly  10% advancement result through conducting portofolio assessment on cognitive, afective, and psychomotor aspect.